Cinderella Weight: Tirani Standar Kecantikan dan Body Image di Kalangan Wanita Muda Jepang - Zahrah, Shafa Tsaniya; Purba, Esther Risma (Humanis; Vol 26 No 4 (2022), 2022)
As a result of the "kawaii" trend, having a slim body has become one of the beauty standards coveted by young Japanese women. One of the latest diet trend in 2016 and 2018 was the Cinderella weight, a weight standard that is considered as dangerous because the weight count is below the healthy BMI (Body Mass Index). This research was conducted using descriptive qualitative methods and video interviews from the Ask Japanese YouTube channel ( 2016, 2020, and 2022) regarding Cinderella weight and ideal body weight of young Japanese women were taken as the main data sources. The Theory of Social Construction of Women's Bodies by Sandra Lee Bartky (1990) was used to analyze this phenomenon and prove that beauty is a form of social construction. It was found that numerous of them idealizing Cinderella weight and being slim is still the desire of the majority of young Japanese women. The role of social media and mass media, which feature many female models and artists who are slim also inseparable for the influence.